PICES Press, Vol. 18, No. 1, Winter 2010 (North Pacific Marine Science Organization (PICES), 2010)
•Major Outcomes from the 2009 PICES Annual Meeting: A Note from the Chairman (pp. 1-3, 8) •PICES Science – 2009 (pp. 4-8) •2009 PICES Awards (pp. 9-10) •New Chairmen in PICES (pp. 11-15) •PICES Interns (p. 15) •The State of the Western North Pacific in the First Half of 2009 (pp. 16-17, 27) •The State of the Northeast Pacific in 2009 (pp. 18-19) •The Bering Sea: Current Status and Recent Events (pp. 20-21) •2009 PICES Summer School on “Satellite Oceanography for the Earth Environment” (pp. 22-25) •2009 International Conference on “Marine Bioinvasions” (pp. 26-27) •A New PICES Working Group Holds Workshop and Meeting in Jeju Island (pp. 28-29) •The Second Marine Ecosystem Model Inter-comparison Workshop (pp. 30-32) •ICES/PICES/UNCOVER Symposium on “Rebuilding Depleted Fish Stocks – Biology, Ecology, Social Science and Management Strategies” (pp. 33-35) •2009 North Pacific Synthesis Workshop (pp. 36-37) •2009 PICES Rapid Assessment Survey (pp. 38-40)